Universal and reconfigurable to UPS active power filter for line conditioning. - Barrero, F. (IEEE Transactions on power delivery)
This paper describes an improved universal active power line conditioner designed to attenuate every disturbance in the electric power system and critical loads, except frequency variations. The circuit has a series voltage filter and a parallel current filter interconnected through a shared DC bus. In case of a supply interruption, the current filter reconfigures to UPS and feeds a preselected 20% of load during 500 ms at the expenses of the DC bus. Over previous reconfigurable solutions, the input and output series static switches have been eliminated improving the reliability, efficiency and cost. Optional parallel LC tuned current filters have also been proved to be control compatible. The search has been guided by an iterative analysis+synthesis cost comparative method, initiated in previous works, showing the cost of the components involved in each explored topology. Experimental results on three laboratory models and a 400 kVA industrial prototype validate the topology and suggest improvement of some control loops.